2017
DOI: 10.1002/qj.3034
|View full text |Cite
|
Sign up to set email alerts
|

The transient atmospheric response to a reduction of sea‐ice cover in the Barents and Kara Seas

Abstract: The observed reduction of Arctic sea-ice has drawn a lot of interest for its potential impact on mid-latitude weather variability. One of the outstanding challenges is to achieve a deeper understanding of the dynamical processes involved in this mechanism.To progress in this area, we have designed and performed an experiment with an intermediate complexity atmospheric model. The experiment shows a transient atmospheric response to a surface diabatic heating in the Barents and Kara seas leading to an anomalous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
1
22
1
Order By: Relevance
“…There remains uncertainty about whether the winter WACS pattern is a delayed response to decreased autumn sea ice , Overland et al 2011, Wegmann et al 2015, Suo et al 2016, Wu 2017) via a stratospheric feedback (Jaiser et al 2012, Cohen et al 2014, García-Serrano et al 2015, Jaiser et al 2016, Ruggieri et al 2017, Kretschmer et al 2017 or if it is an immediate response triggered by winter sea ice anomalies (Hori et al 2011, Inoue et al 2012, Sorokina et al 2016, King et al 2016. The physical feedbacks, as summarized by Cohen et al (2014), are thought to induce a causal chain process, where reduced autumn sea ice warms the lower troposphere, which increases geopotential heights, shifts stormtracks and increases Eurasian snow cover in October and November.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There remains uncertainty about whether the winter WACS pattern is a delayed response to decreased autumn sea ice , Overland et al 2011, Wegmann et al 2015, Suo et al 2016, Wu 2017) via a stratospheric feedback (Jaiser et al 2012, Cohen et al 2014, García-Serrano et al 2015, Jaiser et al 2016, Ruggieri et al 2017, Kretschmer et al 2017 or if it is an immediate response triggered by winter sea ice anomalies (Hori et al 2011, Inoue et al 2012, Sorokina et al 2016, King et al 2016. The physical feedbacks, as summarized by Cohen et al (2014), are thought to induce a causal chain process, where reduced autumn sea ice warms the lower troposphere, which increases geopotential heights, shifts stormtracks and increases Eurasian snow cover in October and November.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies based on sensitivity experiments with atmospheric global climate models (AGCMs) nevertheless question the proposed link between sea ice reduction and the WACS pattern , Sun et al 2016, McCusker et al 2016, Boland et al 2017, Collow et al 2016. On the other hand, some model studies , Nakamura et al 2015, Kretschmer et al 2017, Pedersen et al 2016, Crasemann et al 2017, Ruggieri et al 2017 did indeed show realistic tropospheric sensitivity to sea ice forcing. Cohen et al 2012 as well as Cohen 2016 pointed out that many of the current generation of AGCMs may lack the ability to simulate the influence of Arctic amplification on mid-latitude climate.…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis posed in the 'Introduction' regards pan-Arctic SIE, but recent studies have identified specific Arctic sub-regions that promote geographically varying effects, e.g., ref. 19 For example, anomalies in sea ice over the Barents-Kara Seas have been linked to anomalous large-scale circulation in the Northern Hemisphere during boreal winter specifically 20,21 as well as during other parts of the year. Thus, we investigated the seven regions with non-zero SIE during this month ( Table 2; see Supplement Fig.…”
Section: Figure 1amentioning
confidence: 99%
“…The advance and retreat of the sea-ice edge in the Barents Sea causes strong year-to-year variability in this region. Many earlier studies have highlighted the impact of winter sea-ice loss over this region on midlatitude circulation and climate over Eurasia (Deser, Tomas, and Peng 2007;Gao and Wu 1998;Han and Li 2013;Inoue, Hori, and Takaya 2012;Kug et al 2015;Li and Wang 2012;Liptak and Strong 2013;Mori et al 2014;Ruggieri et al 2017;Screen 2017;Sorokina et al 2015;Wu, Huang, and Gao 2001;Wu et al 2013). Mori et al (2014), for example, revealed a robust winter surface air cooling in midlatitude Asia in response to a lighter sea-ice cover in the Barents Sea.…”
Section: Introductionmentioning
confidence: 98%